Modern trends in diagnostics and treatment of gastroduodenal ulcers - G. K. Zherlov (Бюллетень сибирской медицины, 2003)
In the lecture the modern views on diagnistics and tactic choice in the treatment of complicated and uncomplicated gastroduodenal ulcers have been presented and long-term results of organ-saving and organ-modeling surgery experience during complicated stomach and duodenal ulcers have been analyzed. Achievements in life quality saving of operated patients have been cited. Novel classifications of gastroduodenal anastomosis functional activity and anastomositis degrees have been proposed.